Mycoplasma Pneumonia: An Unrecognized Cause of Fever of Unknown Origin in an Adult. (17th October 2017) - Ali-Ahmed, Fatima; Halalau, Alexandra
Abstract : A 26-year-old female was admitted for fever of unknown origin (FUO), headaches, left ankle edema, and a lower extremity rash consistent with erythema nodosum. She had no respiratory symptoms or family history of autoimmune diseases. A chest X-ray was negative for pneumonia or hilar adenopathy. Extensive autoimmune workup was negative. A chest, abdomen, and pelvis computed tomography scan was unremarkable and laboratory studies revealed no source of infection. On hospital day 5, the patient developed a mild productive cough. Her Mycoplasma pneumonia (MP) IgM was high, confirming the diagnosis of MP induced FUO. She was started on azithromycin 500 mg daily and within 24 hours her fevers and headaches resolved. Her left ankle edema and EN gradually improved over a course of a few weeks. This case report highlights the need for MP testing in the evaluation of fever of unknown origin, even in the absence of pulmonary manifestations.